Home ownership in Southern European countries: Similarities and differences - Botelho Azevedo, Alda (2016)
Southern European countries (SEC) are often considered as a homogenous group, distinct from the rest of Europe, in the literature of housing studies. This article explores the idea that despite sharing cohesion factors, Cyprus, Greece, Italy, Malta, Portugal and Spain also displayed a significant degree of heterogeneity in their housing patterns at the outset of the current economic crisis. The study analyses 2005 and 2009 micro-data from the European Union Statistics on Income and Living Conditions at two levels. At the macro level, a cluster analysis was used to define four homogeneous groups in the European context. At the micro level, both homogeneous and heterogeneous features of home ownership in the SEC were identified using logistic modelling. The results of the macro analysis highlight the structural proximity between the southern and the post-socialist countries in terms of housing characteristics. With regard to predictors of home ownership, the micro analysis confirms that SEC form a distinctive group when compared with the European Union at large, while displaying significant internal heterogeneity in predictors such as age, citizenship, dwelling type and social environment.